Comparison of Output Performance of Tunable Lasers with Two Different External Cavities - Wang, Ya; Zhan, Shengbao; Le, Wenran; Liu, Qinghai; Wang, Yuting; Zou, Lin; Deng, Zhifeng (International Journal of Optics, 2022)
Based on the simplified model of the tunable fiber laser system, the tuning performance of the laser was analyzed. Two kinds of tunable setups were established, which are the configurations with an external cavity and the configuration of the Littrow cavity. The tuning output characteristics experimentally were analyzed by means of setups. The simulation gives the output efficiency of two tunable lasers as 40% and 30%. In the experiment, the measured slope efficiency of the two lasers was 24% and 18.3%, and the tunable range of the two lasers was 32 nm and 40 nm, respectively. Both lasers could achieve laser output with good beam quality.